2018
DOI: 10.1371/journal.pone.0204725
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and correlates of intimate partner violence against female garment workers from selected factories in Bangladesh

Abstract: Intimate partner violence (IPV) is a huge public health, development and human rights issue worldwide. Despite the fact that working women in patriarchal contexts commonly report higher level of IPV, literature on this subject is still scanty. This paper assessed the magnitude of different types of IPV against female garment workers and identified its correlates using cross-sectional survey data collected during September-December, 2016 from 800 female garment workers randomly selected from lists provided by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 54 publications
3
32
0
1
Order By: Relevance
“…First, women were not paid well and worked long hours, and many experienced forms of coercion and economic control from factories. One-fifth (21%), for instance, did not have a letter of appointment, and many experienced factory managers controlling their earnings [ 8 , 21 ]. Second, some female garment workers do not retain control of their earnings.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…First, women were not paid well and worked long hours, and many experienced forms of coercion and economic control from factories. One-fifth (21%), for instance, did not have a letter of appointment, and many experienced factory managers controlling their earnings [ 8 , 21 ]. Second, some female garment workers do not retain control of their earnings.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
“…Second, some female garment workers do not retain control of their earnings. The earnings were either forcefully taken by the husband or handed over by the workers to their husband or mother-in-law [ 8 , 21 ]. As such, a key pathway through which violence could change, was not in operation.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
“…We modified this instrument to use in our study. The tools were previously used in Bangladeshi settings [31]. Mothers and children's height and weight were measured following WHO standards.…”
Section: Measurementmentioning
confidence: 99%
“…The global prevalence of spousal violence is reported through multi-country study lie in range of 23-30% [8]. Review of statistics on prevalence of spousal violence from Pakistan [9] and other developing countries [10,11] have shown that even larger percentage (34-43%) of women experienced physical, psychological and sexual forms of violence in their everyday lives.…”
Section: Introductionmentioning
confidence: 99%